HUBUNGAN PERSEPSI PASIEN MENGENAI MUTU PELAYANAN DENGAN MINAT KUNJUNGAN ULANG PASIEN RAWAT JALAN DI RSUD SANJIWANI GIANYAR TAHUN 2022 - Pradevi, Ni Putu Mirananda; Listyowati, Rina (Program Studi Sarjana Kesehatan Masyarakat Universitas Udayana Berasosiasi Dengan Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI), 2023)
Good service quality will provide satisfaction and good perception to customers which can affect the interest of repeat visits. This study aims to determine the relationship between patient perceptions of service quality and interest in outpatient visits at Sanjiwani Hospital, Gianyar in 2022. The research design used was descriptive quantitative with a cross-sectional. The population in this study were all outpatients who used the services at RSUD Sanjiwani Gianyar from April to May 2022. A sample of 100 people was taken using the total cluster sampling technique. The data collection instrument used a questionnaire. Data analysis was carried out univariate and bivariate. The results showed as many as 34% of respondents were interested in making repeat visits. There was a significant relationship between perceptions of responsiveness (p=0.022), empathy (p=0.044) and physical evidence (p=0.042) with interest in repeat visits. Meanwhile, the dimensions of reliability, assurance and respondent characteristics did not have a significant relationship with the patient's interest in repeat visits (p>0.05). Therefore, an effort is needed from the Sanjiwani Hospital in Gianyar to maintain and improve the quality of services provided so that patients are interested in making repeat visits.Keywords: Service Quality, Interest of Revisits, Perception